Concomitant Aspergillus and Cytomegalovirus infection in heart transplant: early diagnosis is the key to successful treatment - (:unkn) unknown (My University, 2009)
Concomitant infections, which are common in patients who have received an organ transplant, must be diagnosed and treated early to prevent high mortality rates. We describe a case of concomitant Cytomegalovirus infection and Aspergillus pneumonia in a heart transplant patient who received pulsed steroids as therapy for rejection, and we describe the successful treatment of that coinfection with ganciclovir and voriconazole.
Keywords: Humans; Middle Aged; Treatment Outcome; Immunosuppressive Agents; Tomography, X-Ray Computed; Male; Antiviral Agents; Triazoles; Antifungal Agents; Acute Disease; Graft Rejection; Early Diagnosis; Pyrimidines; Voriconazole; Cardiomyopathy, Dilated; Cytomegalovirus Infections; Ganciclovir; Heart Transplantation; Invasive Pulmonary Aspergillosis; Opportunistic Infections; Pulse Therapy, Drug